2021
DOI: 10.1021/acsphotonics.1c00880
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Forward Brillouin Gain in a Hybrid Photonic–Phononic Silicon Waveguide

Abstract: Silicon-based stimulated Brillouin scattering (SBS) promotes the on-chip all-optical signal processing network by interfacing silicon photonic and phononic technologies. Controllable and strong Brillouin coupling in silicon is a key requirement for this purpose. Here, we demonstrate traveling-wave forward SBS and Brillouin gain through a class of hybrid photonic-phononic silicon waveguides on the silicon-on-insulator (SOI) platform. This design combines the advantages of a silicon ridge waveguide and phononic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…20−22 In a hybrid photonic−phononic silicon waveguide, a small-signal Stokes gain of 0.9 dB is realized with only a 1.085 cm length straight waveguide device at moderate pump power. 22 The compact size and high Brillouin gain in the integrated waveguide are critical for future phonon−photon signal processing. This kind of integrated hybrid waveguide provides a universal platform for the investigation of integrated Brillouin photonics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…20−22 In a hybrid photonic−phononic silicon waveguide, a small-signal Stokes gain of 0.9 dB is realized with only a 1.085 cm length straight waveguide device at moderate pump power. 22 The compact size and high Brillouin gain in the integrated waveguide are critical for future phonon−photon signal processing. This kind of integrated hybrid waveguide provides a universal platform for the investigation of integrated Brillouin photonics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To further tailor the dispersion of optical waves, waveguides consisting of periodic structures have been proposed and studied. [41][42][43][44][45][46] Especially, novel optical waveguides formed by chains of silicon nanoparticles have been experimentally demonstrated and are possible to realize advanced functionalities. [47][48][49] Recently, we have also proposed and shown that chain-like silicon waveguides can confine optical waves via the quasi-bound states in the continuum while each silicon unit acts as a mechanical resonator, thus realizing a considerable optomechanical coupling rate.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid progress of optical communication networks relies heavily on two fundamental technologies: high-speed optical transmission and all-optical signal processing. , The advancement of high-speed optical transmission has been remarkable with the reported transmission of a system over 1.8 Pbit/s at a distance of approximately 8 km . As a result, all-optical signal processing is increasingly becoming essential in the construction of high-speed optical fiber communication networks. , All-optical signal processing is a critical operation for optical communication systems and data networks, and it is commonly achieved by utilizing nonlinear optical media such as periodic polarization lithium niobate waveguide (PPLN), sulfide waveguide, , silicon-based waveguide, semiconductor optical amplifier (SOA), etc. While these platforms have achieved notable success, they are not without limitations.…”
Section: Introductionmentioning
confidence: 99%